WebSphere and .NET Coexistence - Kovari, Peter (IBM redbooks., 2004)
This IBM Redbooks publication explores the different coexistence scenarios for the WebSphere and .NET platforms. This book is a good source of information for solution designers and developers, application integrators and developers who wish to integrate solutions on the WebSphere and .NET platforms. Part 1, "Introduction" is a quick introduction to the J2EE (WebSphere) and .NET technologies. It also depicts a basic architectural model that can be used to represent both WebSphere applications and .NET applications. Part 2, "Scenarios" identifies several potential technical scenarios for coexistence via point-to-point integration between applications deployed in the IBM WebSphere Application Server and applications deployed in the Microsoft .NET Framework. This part provides in-depth technical details on how to implement certain scenarios using today's existing technologies. Part 3, "Guidelines" provides general guidelines for solution developers. A list of supporting technologies can help with the solution implementation. The Quality of Service chapter is a collection of services available on both platforms. The Appendixes go further by using other IBM technologies and describing two integration solutions between Lotus Domino and .NET applications. Please note that the additional material referenced in the text is not available from IBM